UJI AKTIVITAS ANTIBAKTERI DAN ANTIOKSIDAN SENYAWA DERIVAT PIRANON DARI MIKROBA ENDOFITIK Penicillium sp PADA TUMBUHAN KUNYIT PUTIH (Curcuma zedoaria (Berg.) Roscoe) - Muharni Muharni; Fitrya Fitrya; Milanti oktaruliza; Elfita Elfita (Majalah Obat Tradisional, 2014)
Exploration of bioactive compound were continuously done as more new diseases appearing, from infection, cancer, and other degenerative diseases. The invention of new antibiotic compound and antioxidant compound is very needed to solve this problem. Endophytic microbes are microbes which lives in plant’s culture and produce the active secondary metabolite. In previous research, 2 compounds from endofitic microbes Penicillium sp in kunyit putih had been successfully isolated and identified as di-(2-ethylhexyl)phthalate   and  pyranon derivated as 5 (4’-ethoxy-2’-hydroxy-5’-methyl-2’,3’-dihydrofuran-3’-il (hydroxy) methyl-4-isopropyl-3-methyl-2-pyran-2-on). The goal of this research is to test antibacterial and antioxidant activitiy from derivate pyranon, which is resulting from endofitic microbes Penicillium sp in kunyit putih (Curcuma zeodaria). The method used to test the antibacterial activity is dic diffusion, using E. Coli, S. Dysenteriae, S. Aureus, and B. Subtilis. with variation of concentrations 250, 500, 1000, dan 2000μg/mL, and to test the antioxidant activity used 1,1-diphenyl-2- picrylhydrazyl ( DPPH)  method with variation of concentrations 1000, 500, 250, 125, 62.5, 31.25, 15.625, and 7.8125 µg/mL. The research         shown that  the antibacterial activity is strongest at S. aureus with 11mm-blocked-zone at 250µg/mL  concentration. Pyranon derivate also has active antioxidant manner with IC5016.05µg/mL.